Paradoxical response of VEGF expression to hypoxia in CSF of patients with ALS. Issue 2 (17th January 2006) - Moreau, C; Devos, D; Brunaud-Danel, V; Defebvre, L; Perez, T; Destée, A; Tonnel, A B; Lassalle, Ph; Just, N
Abstract : Vascular endothelial growth factor (VEGF) is implicated in motor neurone degeneration. In normal individuals, hypoxia is known to induce an overexpression of VEGF, as measured in CSF. We show that patients with ALS do not manifest this VEGF overexpression in the presence of hypoxia. Although VEGF gene expression is mainly stimulated by hypoxia, we have measured lower VEGF levels in cerebrospinal fluid (CSF) from hypoxaemic patients with amyotrophic lateral sclerosis (ALS) than in CSF from normoxaemic patients with ALS. In contrast, hypoxaemic neurological controls displayed higher levels than normoxaemic neurological controls. There was a negative correlation between VEGF levels and the severity of hypoxaemia in patients with ALS, suggesting deregulation of VEGF in ALS.